Deep learning-based real-time pothole detection for avoiding road accident - Basher, Rafsan; Ayon, Asif Raihan; Gharamy, Avijit; Zayed, Abdullah Al; Zaman, Md Samin Yeasar Ibna (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.